2020
DOI: 10.31234/osf.io/ewrtq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A reflection on cognitive reflection – testing convergent validity of two versions of the Cognitive Reflection Test

Abstract: Although it is generally acknowledged that the Cognitive Reflection Test (CRT) captures intelligence and numerical ability, many agree that it cannot be completely reduced to these constructs. Rather, it is presumed that the CRT also assesses some kind of thinking disposition towards reflective and open-minded thinking. In this manuscript, we report the results of a study that tested this assumption by exploring convergent validity of both the numerical and verbal version of the CRT. Using structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
6
19
0
Order By: Relevance
“…However, we also found that CRT performance was more strongly related to intelligence test performance, r = .33, than to need for cognition, r = -.18. This finding is not a fluke in our data, but rather it is consistent with a recent study that systematically evaluated the validity of two CRT versions and concluded that they did not access the construct of cognitive reflection, but rather individual differences in intelligence and numerical abilities (Erceg et al, 2020).…”
Section: Need For Cognition and Cognitive Reflectionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, we also found that CRT performance was more strongly related to intelligence test performance, r = .33, than to need for cognition, r = -.18. This finding is not a fluke in our data, but rather it is consistent with a recent study that systematically evaluated the validity of two CRT versions and concluded that they did not access the construct of cognitive reflection, but rather individual differences in intelligence and numerical abilities (Erceg et al, 2020).…”
Section: Need For Cognition and Cognitive Reflectionsupporting
confidence: 92%
“…In addition to drift rate v and boundary separation a, we also estimated the non-decision time t0 and the trial-to-trial variability of the non-decision time st0. The starting point z was fixed to a/2 and all other model parameters 1 The current debate regarding the CRT reflects uncertainty regarding its validity: While some argue that the CRT measures individual differences in reflective thinking ability (Frederick, 2005), others argue that it largely measures cognitive and numerical abilities (Blacksmith et al, 2019;Erceg et al, 2020). Undoubtedly, however, performance in the CRT predicts susceptibility to biases and logical fallacies (e.g., Bialek & Pennycook, 2018;Pennycook & Ross, 2016), making it an important measure to consider in any study on individual differences in bias susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Univariate analysis also found common correlations. Reflection test performance correlated with numeracy (Attali & Bar-Hillel, 2020;Białek, Bergelt, et al, 2019;Białek & Sawicki, 2018;Erceg et al, 2020;Patel, 2017;Szaszi et al, 2017), morality Patil et al, 2018;Reynolds et al, 2019), political orientation (Deppe et al, 2015;Yilmaz et al, 2019), and theism (Gervais et al, 2018;Pennycook et al, 2016). Further, older people were more conservative (Cornelis et al, 2009;Luberti et al, 2020) and women were less likely to endorse instrumental harm (e.g., Friesdorf et al, 2015).…”
Section: Univariate Analysismentioning
confidence: 99%